Police Body-Worn Cameras: Perceptions of Law Enforcement Leadership - Smykla, John Ortiz (American journal of criminal justice, 2016)
Many people are enthusiastic about the potential benefits of police body-worn cameras (BWC). Despite this enthusiasm, however, there has been no research on law enforcement command staff perceptions of BWCs. Given the importance that law enforcement leadership plays in the decision to adopt and implement BWCs, it is necessary to assess their perceptions. This is the first study to measure law enforcement leadership attitudes toward BWCs. The study relies on data collected from surveys administered to command staff representing local, state and federal law enforcement agencies in a large southern county. Among the major perceptual findings are that command staff believe BWCs will impact police officers’ decisions to use force in encounters with citizens and police will be more reluctant to use necessary force in encounters with the public. Respondents also believe that use of BWCs is supported by the public because society does not trust police, media will use BWC data to embarrass police, and pressure to implement BWCs comes from the media. Perceptions of the impact of BWCs on safety, privacy, and police effectiveness are also discussed.